The Impact of Scientific Research Activities on the Development of Soft Skills Among University Students in Vietnam - Le Thi, Quynh Trang (Journal Of Education And Teaching Learning (JETL), 2025)
This study focuses on analyzing the impact of scientific research activities on the development of soft skills among university students in Vietnam, with particular emphasis on communication, teamwork, problem-solving, and critical thinking skills. A mixed-methods approach was employed, combining a quantitative survey of 480 students with in-depth interviews involving 20 students who had participated in scientific research, as well as 50 faculty members and administrative staff from various universities. Quantitative data were processed using SPSS software, while qualitative data were analyzed through content analysis. The findings indicate a clearly positive effect of engaging in scientific research on students’ soft skills development: 78% of students reported significant improvement in communication skills; 72% enhanced their teamwork abilities; 69% demonstrated better problem-solving capacity; and 65% reported more logical and refined critical thinking. Based on these results, the study proposes several strategic directions to strengthen the integration of research activities into higher education curricula. These include expanding opportunities for students to participate in interdisciplinary research projects, developing digital platforms to support student-initiated research, and implementing structured mentoring programs between faculty and students. These initiatives are expected to contribute to the enhancement of human resource quality in the context of global integration.